Pengaruh Penerapan Efektivitas Dan Kepercayaan Atas Sistem Informasi Akuntansi, Pemanfaatan Teknologi Dan Kompensasi Sumber Daya Manusia Terhadap Kinerja Karyawan Bank BRI Lampung Tengah - Leni, Leni; Zanaria, Yulita; Kurniawan, Angga (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of implementating effectiveness and trust in accounting information systems, technology utilization and human resource compensation on employee performance at Bank BRI, Central Lampung. This type of research is quantitative research. The instruments used in this study were questionnaires and observations. The data analysis technique performed is using multiple regression analysis. The results of the study show that the Effectiveness of SIA Implementating has a positive and significant impact on employee performance. SIA trust has a positive and significant influence on employee performance. The use of technology has a positive and significant impact on employee performance. Compensation has a positive and significant impact on employee performance